Untimely bodies, untimely aesthetics : temporality, relationality, and intimacy in the cinema of the Berlin School - Pfleger, Simone (McGill-Queen's University Press, 2023)
"While heteronormativity continues to permeate nearly all threads of the socio-cultural fabric, several early twenty-first-century German films offer insight into how we might challenge that dominance and disrupt its linear construction of time. Examining the fluidity of time in eight contemporary films of the Berlin School, Untimely Bodies, Untimely Aesthetics foregrounds how queer conceptualizations of temporality can engage notions of subjectivity, relationality, and intimacy in visual representations. Each film depicts figures that grapple with an unattainable desire for connection, placed in landscapes shaped by hegemonic heteronormative intimacies, and a linear temporal organization of life that conforms to mainstream, traditional rhythms, and milestones. Simone Pfleger proposes a new model for viewing non-normative relationality and intimacies, using the concept of "untimeliness" as an analytical framework for examining content and aesthetics. In these films, untimeliness provides an alternative to the romanticization of progress by charting how the filmic figures understand themselves and relate to one another in various spheres: work, love, sex, home, family, and self. Ultimately, Pfleger shows how the texts uncover a temporary promise of breaking free from restrictive social structures, even as they make clear that this schism cannot and should not be permanent. By proposing time as a critical lens through which to investigate our relationships and intimacies, Untimely Bodies, Untimely Aesthetics offers a new way to think about film and encourages moviegoers to turn the analysis back toward themselves and their own desires, expectations, assumptions, and adherence to or deviation from normative narratives in their own lives."--